Design and Build Inventory Management Information System with Personal Extreme Programming Method - Fiqar, Tegar Palyus; Raphi, Andi Sultan Asharil; Azhar, Nur Fajri (Geuthèë Institute, 2023)
Every company and agency has facilities and infrastructure that play an important role in supporting operational activities. Similar to other institutions, the Kalimantan Institute of Technology also has facilities and infrastructure that need to be managed. The Kalimantan Institute of Technology has not fully implemented the Inventory management process properly, where data on facilities and infrastructure have not been stored into the database and in the loan process they still use Microsoft Excel as storage media which makes it difficult to manage facilities and infrastructure from the Kalimantan Institute of Technology. The method used in this research is the Personal Extreme Programming (PXP) method which consists of several stages, namely requirements, planning, iteration initialization, design, implementation (unit testing, code, refactor), system testing, retrospective. Development of an Inventory Management Information System using framework and developed several features such as facilities and infrastructure management, loan management, and other supporting features. The development of an Inventory Management Information System is expected to provide convenience to the Kalimantan Institute of Technology in managing facilities and infrastructure.